Combined PI3K/Akt and Hsp90 targeting synergistically suppresses essential functions of alloreactive T cells and increases Tregs. Issue 6 (11th August 2015) - Berges, Carsten; Bedke, Tanja; Stuehler, Claudia; Khanna, Nina; Zehnter, Sarah; Kruhm, Michaela; Winter, Nadine; Bargou, Ralf C.; Topp, Max S.; Einsele, Hermann; Chatterjee, Manik
Abstract : Combined Hsp90/PI3K/Akt inhibition, a novel therapeutic strategy for preventing and treating aGvHD in ASCT while sparing beneficial pathogen and primary disease‐specific T cell immunity. Abstract : Acute graft‐versus‐host disease is still a major cause of transplant‐related mortality after allogeneic stem cell transplantation. It requires immunosuppressive treatments that broadly abrogate T cell responses, including beneficial ones directed against tumor cells or infective pathogens. Inhibition of the heat shock protein of 90 kDa has been demonstrated to eliminate tumor cells, as well as alloreactive T cells while preserving antiviral T cell immunity. Here, we show that the suppressive effects of heat shock protein of 90 kDa inhibition on alloreactive T cells were synergistically enhanced by concomitant inhibition of the PI3K/Akt signaling pathway, which is also strongly activated upon allogeneic stimulation. Molecular analyses revealed that this antiproliferative effect was mainly mediated by induction of cell‐cycle arrest and apoptosis. In addition, we observed an increased proportion of activated regulatory T cells, which critically contribute to acute graft‐versus‐host disease control, upon combined heat shock protein of 90 kDa/Akt isoforms 1 and 2 or heat shock protein of 90 kDa/PI3K/p110δ isoform inhibition. Moreover, antiviral T cell immunity was functionally preserved after combined heat shock protein of 90 kDa/Akt isoforms 1 and 2 inhibition. Taken together, our data suggest that the combined heat shock protein of 90 kDa/PI3K/Akt inhibition approach represents a reasonable dual strategy to suppress residual tumor growth and efficiently deplete alloreactive T cells and thus, provide a rationale to prevent and treat acute graft‐versus‐host disease selectively without impairing pathogen‐specific T cell immunity.